2019
DOI: 10.1111/jcmm.14775
|View full text |Cite|
|
Sign up to set email alerts
|

Melittin inhibits proliferation, migration and invasion of bladder cancer cells by regulating key genes based on bioinformatics and experimental assays

Abstract: The antitumour effect of melittin (MEL) has recently attracted considerable attention. Nonetheless, information regarding the functional role of MEL in bladder cancer (BC) is currently limited. Herein, we investigated the effect of MEL on critical module genes identified in BC. In total, 2015 and 4679 differentially expressed genes (DEGs) associated with BC were identified from the GSE31189 set and The Cancer Genome Atlas database, respectively. GSE‐identified DEGs were mapped and analysed using Gene Ontology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…As clearly depicted, FLV-MEL nano-conjugates treatment strongly inhibited the proliferation of OVCAR3 cells, measured by the reduction of G1→S transition as well as the inhibition of the transition from G2 to M phase. These effects could depend on the ability of MEL to suppress the proliferation of cancer cells ( Tipgomut et al, 2018 ; Ceremuga et al, 2020 ; Yao et al, 2020 ) which acts synergistically with FLV ( Hillyard et al, 2002 ; Garwood et al, 2010 ; Hwang et al, 2017 ) even when used at a sub-toxic concentration.…”
Section: Discussionmentioning
confidence: 99%
“…As clearly depicted, FLV-MEL nano-conjugates treatment strongly inhibited the proliferation of OVCAR3 cells, measured by the reduction of G1→S transition as well as the inhibition of the transition from G2 to M phase. These effects could depend on the ability of MEL to suppress the proliferation of cancer cells ( Tipgomut et al, 2018 ; Ceremuga et al, 2020 ; Yao et al, 2020 ) which acts synergistically with FLV ( Hillyard et al, 2002 ; Garwood et al, 2010 ; Hwang et al, 2017 ) even when used at a sub-toxic concentration.…”
Section: Discussionmentioning
confidence: 99%
“… 24 These findings could confirm our conclusions from another perspective. Meanwhile, according to previous studies, we found that TPM1 , 25 SYNM , 26 CSRP1 , 27 CFL2 , 28 HIP1R 29 are often found in the cancer genetic sequence of bladder cancer. 16 , 30 The protein encoded by TPM1 is a member of the widely distributed actin‐binding protein myosin (Tm) family, which participates in the contractile system of striated and smooth muscles and the cytoskeleton of non‐muscle cells, and studies have shown that TPM1 is a tumor suppressor gene 31 and plays a role in inhibiting the development of bladder urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 60%
“…Four cascades exist in the MAPK signaling pathway: ERK1/2, p38 MAPK, c-Jun N-terminal kinase (JNK), and ERK5 (26). It has been shown that p38is involved in the invasion and metastasis of breast cancer ( 27), while ERK5 is involved in both cell proliferation in prostate cancer (28) and cell proliferation, migration, and invasion in bladder cancer (29). The focal adhesion signaling pathway has also been found to be related to the tumorigenesis and progression of various cancers (30).…”
Section: Discussionmentioning
confidence: 99%